Uterine Arteriovenous Malformation: A Near-Missed Fatal Misdiagnosis? - Cindy Chin; Dayang Corieza Febriany (Penerbit UMS, 2023)
Less than 100 cases of uterine arteriovenous malformations (AVM) have been documented. The true incidence remains unknown with 30% complicated by hypovolemic shock. Women who experience unexplained vaginal bleeding may consider this diagnosis. We chose to emphasize this case because, while being a rare disease, it could cause mortality if misdiagnosed. In this case, a 23-year-old lady, para 1+2 with a history of several miscarriages and curettage, complained of per vaginal bleeding more than 2 months after her suction and curettage on September 2018. Her second visit was managed as having retained the product of conception and another curettage was conducted. Despite this, the patient still has worsening vaginal bleeding which leads to her third visit. A bedside ultrasound was conducted and suspected uterine AVM. This was then further confirmed with contrastenhanced computed tomography of the pelvis and pelvis angiography. Five Micronester coils and 10% Histoacryl adhesive were used to successfully embolize the uterine artery. This case report served as a valuable lesson on the importance of having a proper diagnosis and prompt treatment to avoid fatal misdiagnosis which could have disastrous consequences.